Evaluation and development : proceedings of the 1994 World Bank conference - Picciotto, Robert; Rist, Ray C.; World Bank. (Washington, D.C. : World Bank, 1995)
This book makes available the papers presented to the conference and includes the main comments of discussants and other paticipants. The collection reflects the views, concerns, and ambitions of experienced practitioners and evaluators.
"World Bank Operations Evaluation Department"--Cover.
Includes bibliographical references.
rpm 10/06/2015
Loans
Keywords: Economic development projects; Rural development projects; Evaluation research (Social action programs)